1994
DOI: 10.1152/advances.1994.266.6.s2
|View full text |Cite
|
Sign up to set email alerts
|

A computer simulation for learning about the physiological response to exercise.

Abstract: An interactive computer program written for IBM-compatible microcomputers, which simulates the physiological response to graded exercise in healthy individuals, is described. The program presents high-resolution graphic data (heart rate, pulmonary ventilation, oxygen consumption, and blood lactate concentration) in a form comparable to that of a chart recorder display. Data are derived from an empirical model that allows users to select certain parameters of the subject they wish to investigate, including sex,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…The results of this investigation agree with previous studies that have demonstrated that laboratory simulations benefit anesthesiology students (7,14), veterinary students (6,17), occupational therapy students (19), undergraduate exercise science students (3,10), and various other types of undergraduate students (2,4,11,12). It is important to mention that one investigation (8) has provided evidence that computer simulations do not enhance student learning as much as textbook readings.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results of this investigation agree with previous studies that have demonstrated that laboratory simulations benefit anesthesiology students (7,14), veterinary students (6,17), occupational therapy students (19), undergraduate exercise science students (3,10), and various other types of undergraduate students (2,4,11,12). It is important to mention that one investigation (8) has provided evidence that computer simulations do not enhance student learning as much as textbook readings.…”
Section: Discussionsupporting
confidence: 88%
“…Numerous investigations (3-5, 10, 13, 15, 18) have reported that students enjoy working with physiology laboratory simulations and, in some cases, may actually prefer them to traditional laboratory experiences (3,4,13,18). It is important to note that, in those latter four investigations (3,4,13,18), the preference for simulations was largely attributed to the fact that simulations do not require animals to be killed. That justification does not apply to the types of laboratory activities explored in this investigation, however, because human subjects are typically used.…”
Section: Discussionmentioning
confidence: 99%
“…In this study student learning, as measured by answers to key questions, is comparable for both groups, while the cost of the live laboratory is significantly higher. The findings of this study are similar to those of similar studies where computer-based learning methods have been compared to traditional live laboratories in undergraduate physiology and anatomy Coleman et al, 1994;Guy & Frisby, 1992;Fawver et al, 1990).…”
Section: Discussionsupporting
confidence: 86%
“…The succesful use of computer-based simulations to facilitate the retention of knowledge and promote active learning has been well documented (9,12,15,18,19,31,32,34,36,40,54). Also, virtual laboratories can instruct students as effectively as hands-on laboratories (9,15,16,18).…”
Section: Ribarič S Kordaš Mmentioning
confidence: 99%
“…Therefore, contemporary teaching should put more emphasis on teaching modules that develop the student's ability to apply information and develop a better understanding of physiology concepts, thus ensuring the desired educational outcome for the future health professional (10). Practically oriented teaching modules that promote active learning, and are complimentary to lectures, can enhance the student's understanding of concepts (7,20,21,37).The succesful use of computer-based simulations to facilitate the retention of knowledge and promote active learning has been well documented (9,12,15,18,19,31,32,34,36,40,54). Also, virtual laboratories can instruct students as effectively as hands-on laboratories (9,15,16,18).…”
mentioning
confidence: 99%